Regional Language Studies. Newfoundland, Number 20 (15 October 2007) - Overton, James, 1943-; Simmonds, Tara; Story, G. M. (George Morley), 1927-1994 (Memorial University of Newfoundland. Department of English Language and Literature, 2007)
Heaving the rubber boot: the political uses of development follies / James Overton -- Tickle in Eastern Canadian place-names / William J. Kirwin -- Devil-related toponymy and etymology in Newfoundland / Tara Simmonds -- From the archives: Observations on the sources of the Dictionary of Newfoundland English / G.M. Story - Miscellany / William J. Kirwin -- Newfy: supplementary evidence to DNE, 2nd ed. -- Bibliography -- Index to RLS, Numbers 10 to 20.